Journalistic epistemology and digital news circulation: Infrastructure, circulation practices, and epistemic contests. (February 2020) - Carlson, Matt
The digital media environment provokes many questions about the state of journalism as a knowledge producing practice. As a means to better assess how changing digital news practices connect to journalists' epistemic authority, this article combines Ekström's emphasis on journalistic epistemology as a social practice of knowledge production with Bødker's conceptualization of circulation both as a form of information transmission and as a site for producing shared meanings about journalism. To develop a model for analyzing the epistemic consequences of digital news circulation, three components of circulation are explored: infrastructure, circulation practices, and epistemic contests. These components consider, respectively, the materiality of digital media, various usage patterns that arise, and public struggles over what news as a form of knowledge ought to look like and who should produce it.